Adventureman. Volume 1, "The end and everything after" - Fraction, Matt; Fraction, Matt; Dodson, Terry (Image Comics, Inc., 2020)
"Where his story ended... her story begins! Everyone knows the story of how Adventureman, the greatest pulp hero of ended in a heartbreaking cliffhanger with our hero facing his very execution... now learn the startling truth about what came next! Decades after his seeming demise, the world has forgotten all about Adventureman--save for single mother Claire and her Adventurefan son Tommy, Together, they'll light the spark of Adventureman's resurrection... but if the good guys are coming back, you can bet the bad guys won't be far behind."--Provided by publisher.